2020
DOI: 10.21203/rs.3.rs-31237/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severe colon ischemia in patients with severe COVID-2019 infection: a report of three cases

Abstract: Severe disease caused by the SARS-CoV coronavirus is characterized by patients presenting with respiratory distress associated with a systemic inflammatory response syndrome (cytokine storm). Sixteen to thirty percent of COVID-19 patients also have gastrointestinal symptoms. Here we present three cases of COVID-19 who developed colonic ischemia. Three males aged 76, 68 and 56 with respiratory distress and receiving mechanical ventilation presented episodes of rectal bleeding, abdominal distension and signs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Since the COVID-19 can intervene in intravascular systems, the majority of all deaths in patients with COVID-19 are attributed to VTE and disseminated intravascular coagulation (DIC) which are consequences of the systemic inflammatory response [ 26 , 27 ]. PTE is also associated with marked changes in some laboratory markers such as D-dimer and LDH according to recent radiologic surveys [ 28 , 29 ], that is why proper anticoagulant treatment to reduce PTE complications in COVID-19 patients is so crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Since the COVID-19 can intervene in intravascular systems, the majority of all deaths in patients with COVID-19 are attributed to VTE and disseminated intravascular coagulation (DIC) which are consequences of the systemic inflammatory response [ 26 , 27 ]. PTE is also associated with marked changes in some laboratory markers such as D-dimer and LDH according to recent radiologic surveys [ 28 , 29 ], that is why proper anticoagulant treatment to reduce PTE complications in COVID-19 patients is so crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Rashid et al [10], Faridi et al [11], Sevella et al [12], and Shahid et al [13] also confirmed these findings. Almeida et al also described three patients with intestinal ischemia and pneumoperitoneum and showed that the pathogenicity of COVID-19 has been increasingly attributed to the systemic inflammatory response leading to intravascular disseminated coagulation [14].…”
Section: Discussionmentioning
confidence: 99%